Extragastrointestinal stromal tumors of the pelvic cavity and the vagina: Two case reports and review of the literature - Wissam Hanayneh; Jason Starr; Thomas J. George, Jr; Hiral Parekh (Elsevier, 2018)
Gastrointestinal stromal tumors (GISTs) are rare tumors of gastrointestinal (GI) tract with mesenchymal cell origin. Extragastrointestinal stromal tumors (EGISTs) are unusual tumors that exhibit the same immunohistochemical and genetic abnormalities as GISTs and most commonly affect the omentum and mesentery. EGISTs of the pelvis and the female reproductive system are exceedingly rare and a frequent diagnostic pitfall. In this report, we present two cases of EGISTs along with a review of the literature. Keywords: Extragastrointestinal stromal tumor, Vagina, Pelvic cavity